(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article discusses the issues of repetition, which allows English teachers and parents to optimize the learning of kindergarten and lower elementary school students. The use of recognizable and fun pedagogy leads to improved skills in several skill areas, as well as a positive attitude towards learning in general.